Development of Fun Multiplication Learning Media with Snakes and Ladders and Multiplication Cards to Improve Cognitive Abilities of Grade IV Elementary School Students - Eka Sari Pancasilawati; Sutopo, Yeri; Yuwono, Agus (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2025)
This research was motivated by the low cognitive ability of students in learning mathematics in multiplication. The purpose of this study was to develop a learning medium called “Fun Multiplication with Snakes and Ladders and Multiplication Cards” (PADUKA) and to test its feasibility, practicality, and effectiveness in improving the cognitive ability of fourth-grade elementary school students. This study used the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The research subjects comprised 16 students in the experimental class and 22 in the control class. The data collection techniques used tests, questionnaires, and observations. The results showed that: (1) PADUKA media is declared feasible by media experts and subject matter experts; (2) PADUKA media is practically used in learning based on positive responses from teachers and students; (3) PADUKA media is effective in improving students' cognitive abilities with an N-Gain value of 0.65 (moderate category) and an effectiveness value of 91.1% (very high category). The paired t-test shows a significant difference between the pretest and posttest scores (p=0.000), and the independent samples t-test shows a significant difference between the experimental and control classes (p=0.005). Based on these results, it is recommended that PADUKA media be implemented more widely in mathematics learning in elementary schools.